Melanoma RBPome identification reveals PDIA6 as an unconventional RNA-binding protein involved in metastasis. Issue 14 (15th July 2022) - Mestre-Farràs, Neus; Guerrero, Santiago; Bley, Nadine; Rivero, Ezequiel; Coll, Olga; Borràs, Eva; Sabidó, Eduard; Indacochea, Alberto; Casillas-Serra, Carlos; Järvelin, Aino I; Oliva, Baldomero; Castello, Alfredo; et al.
Abstract: RNA-binding proteins (RBPs) have been relatively overlooked in cancer research despite their contribution to virtually every cancer hallmark. Here, we use RNA interactome capture (RIC) to characterize the melanoma RBPome and uncover novel RBPs involved in melanoma progression. Comparison of RIC profiles of a non-tumoral versus a metastatic cell line revealed prevalent changes in RNA-binding capacities that were not associated with changes in RBP levels. Extensive functional validation of a selected group of 24 RBPs using five different in vitro assays unveiled unanticipated roles of RBPs in melanoma malignancy. As proof-of-principle we focused on PDIA6, an ER-lumen chaperone that displayed a novel RNA-binding activity. We show that PDIA6 is involved in metastatic progression, map its RNA-binding domain, and find that RNA binding is required for PDIA6 tumorigenic properties. These results exemplify how RIC technologies can be harnessed to uncover novel vulnerabilities of cancer cells.